2012
DOI: 10.1371/journal.pone.0041720
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reduced Rotavirus Vaccine Efficacy in Low Socio-Economic Settings

Abstract: IntroductionRotavirus vaccine efficacy ranges from >90% in high socio-economic settings (SES) to 50% in low SES. With the imminent introduction of rotavirus vaccine in low SES countries, understanding reasons for reduced efficacy in these settings could identify strategies to improve vaccine performance.MethodsWe developed a mathematical model to predict rotavirus vaccine efficacy in high, middle and low SES based on data specific for each setting on incidence, protection conferred by natural infection and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 39 publications
3
124
0
2
Order By: Relevance
“…[2] estimated that rotavirus vaccine could result in 2.46 million childhood deaths between 2011-2030. Of course, uncertainty in the seroconversion rate [24] and achievable vaccination coverage means that the true benefit of these vaccines is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] estimated that rotavirus vaccine could result in 2.46 million childhood deaths between 2011-2030. Of course, uncertainty in the seroconversion rate [24] and achievable vaccination coverage means that the true benefit of these vaccines is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To reflect this uncertainty, we investigate the impact of vaccination using the value of efficacy from two different studies. First based on the results of [24], for low income countries, we assume a seroconversion rate of 63%. Second, a recent study of a 3-dose vaccination strategy in Niger [20] estimated efficacy of 66.7% with all doses.…”
Section: Vaccinationmentioning
confidence: 99%
“…17,48,73,74 Increasing the number of rotavirus vaccine doses Waning vaccine efficacy from one year post-immunisation may be addressed through the administration of additional vaccine doses. 75 Lopman et al proposed that extra vaccine doses later in the EPI schedule may target the severe symptomatic nature of higher-order infections in low-income countries, estimating a 9% improvement in RV1 vaccine efficacy with a 3-dose course at 6, 10 and 14 weeks. 75 This is supported by a previous study that demonstrated that the same 3-dose RV1 course was efficacious against severe rotavirus gastroenteritis, without an increased risk of intussusception following the third dose.…”
Section: Changes To Rotavirus Immunisation Schedulesmentioning
confidence: 99%
“…75 Lopman et al proposed that extra vaccine doses later in the EPI schedule may target the severe symptomatic nature of higher-order infections in low-income countries, estimating a 9% improvement in RV1 vaccine efficacy with a 3-dose course at 6, 10 and 14 weeks. 75 This is supported by a previous study that demonstrated that the same 3-dose RV1 course was efficacious against severe rotavirus gastroenteritis, without an increased risk of intussusception following the third dose. 29 The administration of an additional dose at a later age, such as concomitantly with measles-containing vaccines at 9 months of age, may pose a potential solution to the observed decreased efficacy in the 2 nd year of life.…”
Section: Changes To Rotavirus Immunisation Schedulesmentioning
confidence: 99%
“…A growing body of evidence now suggests that gut microbiota may also play an important role in determining vaccine efficacy. Studies have demonstrated that immunogenicity of oral vaccines against cholera [2,3], rotavirus [4] and polio [5] is lower in populations from regions with poor sanitation who have a higher occurrence of fecal-oral bacterial exposure. While this observation may be confounded by factors such as socioeconomic status, genetics or malnutrition, the prevailing hypothesis is that exposure to harmful microbes could alter the composition of bacteria in the gut [6], and the composition of the gut may influence vaccine immunogenicity.…”
mentioning
confidence: 99%